Lessons Learned from Responsibility to Protect (R2P) in Libya - Fadhila Inas Pratiwi (Global Strategis, 2017)
As a new principle in the world, Responsibility to Protect (R2P) is an obligation on the part of the international community and on the part of the states to protect civilians from mass atrocities by doing several actions like giving international aids, reducing poverty, supporting peacebuilding, educating the population, until military intervention. However, military intervention under R2P norm in Libya produce a counterproductive result which then led the country into civil war. From this background, therefore, the purpose of this article is to examine the implementation of R2P in Libya into four types of lessons learned. The first lesson, R2P is corrupted by great powers that make the military intervention far from its mandate. The second lesson is the inconsistency practice from an R2P military intervention which led to the question of credibility of military intervention in Libya. The third lesson is diplomacy must be prioritized rather than military intervention since that there is an R2P success story without military intervention. The last is the recommendation to implement Responsibility while Protecting (RWP) principle in the R2P framework.Keywords: Responsibility to Protect (R2P), Libya, Diplomacy, Military Intervention, Responsibility while Protecting